calcined body
Patent Information
- Application Number
- CN202480029113.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2023-03-15
- Filing Date
- 2024-02-29
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-02-29
AI Technical Summary
[0034]本发明的煅烧体产生光子。
Smart Images

Figure CN121039246B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to calcined products. Background Technology
[0002] It is well known that compositions containing platinum produce far-infrared rays. Far-infrared rays are electromagnetic waves that radiate / emit wavelengths in the range of a few μm to approximately 400 μm, exhibiting excellent heating and drying effects. Therefore, ceramics, as far-infrared radiators, can heat evenly to the interior without overheating the surface, and are thus effectively utilized in high-quality food processing. Furthermore, fibers with far-infrared effects, formed by incorporating far-infrared radiating materials into fibers or coating them onto surfaces, are widely used in bedding, suits, underwear, and other products.
[0003] For example, Japanese Patent Application Publication No. 62-184088 states that far-infrared radiating powder containing alumina, silicon dioxide, and crude platinum has the effect of improving the shelf life and taste of food products.
[0004] Japanese Patent Application Publication No. 3-190990 describes a powder containing aluminum oxide, titanium, and crude platinum that emits weak infrared energy, which is effective in extending the shelf life of food products. It also states that synthetic fibers containing this powder promote blood circulation, have a warming effect, and are effective for symptoms such as cold intolerance and joint pain.
[0005] Furthermore, Japanese Patent Application Publications Nos. 3-241025 and 4-73226 disclose that woven fabrics made from nylon or polyester fibers obtained by mixing far-infrared radiating powder formed from alumina, silica, and coarse platinum are extremely effective in maintaining the body's warmth.
[0006] Subsequently, a composition containing platinum was reported that, in addition to far-infrared radiation, also produces photons and negative ions.
[0007] For example, Patent Document 5 confirms that a composition containing alumina, silicon dioxide, titanium dioxide, platinum and silver generates far-infrared rays and photons, describes that the composition has excellent antibacterial / bactericidal properties, and describes that fiber products made by mixing the composition into fibers have static electricity removal properties.
[0008] Patent document 6 describes a composition containing aluminum oxide, silicon dioxide, titanium oxide, platinum and silver that generates negative ions, exerts antibacterial properties, and exerts antithrombotic properties by using clothing or bedding made of fibers containing the composition.
[0009] Patent document 7 describes a calcined body comprising a composition of at least one of the following: alumina, silica and titanium dioxide, platinum, platinum compounds, palladium, palladium compounds, iridium, iridium compounds, rhodium and rhodium compounds, barium feldspar and talc, which generates photons and ions and exerts health-enhancing effects such as reducing blood lactate concentration, improving immunity, and reducing lipid peroxidation.
[0010] However, the goal is to increase the amount of photons produced.
[0011] Existing technical documents
[0012] Patent documents
[0013] Patent Document 1: Japanese Patent Application Publication No. 62-184088
[0014] Patent Document 2: Japanese Patent Application Publication No. 3-190990
[0015] Patent Document 3: Japanese Patent Application Publication No. 3-241025
[0016] Patent Document 4: Japanese Patent Application Publication No. 4-73226
[0017] Patent Document 5: Japanese Patent No. 4195562
[0018] Patent Document 6: Japanese Patent No. 4712378
[0019] Patent Document 7: Japanese Patent No. 6606213 Summary of the Invention
[0020] The problem the invention aims to solve
[0021] The purpose of this invention is to provide a calcined body that generates photons.
[0022] Solution for solving the problem
[0023] Examples of the present invention include the following [1] to [8].
[0024] [1] A calcined body comprising: (i) alumina; (ii) at least one selected from the group consisting of silicon dioxide and titanium oxide; (iii) at least one selected from the group consisting of platinum, platinum compounds, palladium, palladium compounds, iridium, iridium compounds, rhodium and rhodium compounds; and (iv) silicon nitride.
[0025] The composition contains 5 to 10 parts by weight of (iv) silicon nitride in 100 parts by weight.
[0026] [2] The calcined body according to [1] further comprises (v) at least one selected from the group consisting of silver, silver compounds, gold and gold compounds.
[0027] [3] According to the calcined body of [1], it also contains (vi) barium feldspar.
[0028] [4] According to the calcined body of [1], it also contains (vii) block talc.
[0029] [5] According to [1], the calcined body is granular and has an average particle size of less than 0.1 μm.
[0030] [6] According to [1] the calcined body, wherein component (iii) contains platinum or a platinum compound.
[0031] [7] A fiber comprising a calcined body of any one of [1] to [6].
[0032] [8] A thin film comprising a calcined body of any one of [1] to [6].
[0033] The effects of the invention
[0034] The calcined body of the present invention generates photons. Attached Figure Description
[0035] Figure 1 This is a graph showing the results of measuring the photon generation of the calcined body (average particle size less than 0.1 μm) obtained in Example 1 using an ultra-weak emission spectrometer CLA-FS4 (manufactured by Tohoku Electronic Industrial Co., Ltd.) and a sample chamber CLS-ST4 (manufactured by Tohoku Electronic Industrial Co., Ltd.).
[0036] Figure 2 This is a graph showing the results of measuring the photon generation of the calcined body (average particle size less than 0.1 μm) obtained in Comparative Example 1 using an ultra-weak emission spectrometer CLA-FS4 (manufactured by Tohoku Electronic Industrial Co., Ltd.) and a sample chamber CLS-ST4 (manufactured by Tohoku Electronic Industrial Co., Ltd.).
[0037] Figure 3This is a graph showing the results of measuring the photon generation of the calcined body (average particle size less than 0.1 μm) obtained in Example 1 using an ultra-weak emission spectrometer CLA-FS5 (manufactured by Tohoku Electronic Industrial Co., Ltd.) and a sample chamber CLS-ST5 (manufactured by Tohoku Electronic Industrial Co., Ltd.). Detailed Implementation
[0038] The present invention relates to a calcined body comprising: (i) alumina; (ii) at least one selected from the group consisting of silicon dioxide and titanium oxide; (iii) at least one selected from the group consisting of platinum, platinum compounds, palladium, palladium compounds, iridium, iridium compounds, rhodium and rhodium compounds; and (iv) silicon nitride, comprising 5 to 10 parts by mass of (iv) silicon nitride in 100 parts by mass of the composition.
[0039] The composition of the present invention preferably further comprises (v) at least one selected from the group consisting of silver, silver compounds, gold and gold compounds.
[0040] <Component (i) Alumina>
[0041] The composition comprising the calcined body of the present invention contains alumina.
[0042] The preferred alumina (Al2O3) is a high-purity alumina with a purity of 99.9% or higher that exhibits excellent sinterability. Commercially available powdered high-purity alumina can be used as the alumina. Because alumina is porous, it is believed that in addition to its own physical properties, it also has the effect of supporting components (iii) and arbitrary components (vi).
[0043] Furthermore, the average particle size of component (i) depends on the product using the calcined body of the present invention and the manner of use, but a common particle size, such as 0.1 to a few μm, can be used. When used incorporating fibers, the average particle size of component (i) depends on the fiber diameter, ideally adjusted to preferably 2 μm or less, more preferably 1.5 μm or less, and even more preferably less than 1.0 μm, for example, about 0.3 μm. It should be noted that in this specification, the average particle size is a value obtained by laser diffraction scattering.
[0044] In 100 parts by mass of the composition, the content of the aforementioned component (i) is preferably 20 to 60 parts by mass, more preferably 25 to 50 parts by mass. If the content of component (i) is within the above range, the generation of photons can be improved. It should be noted that, in this specification, 100 parts by mass of the composition refers to 100 parts by mass of the solid component, such as a liquid such as a suspension medium that does not contain component (iii) in colloidal form.
[0045] <Component (ii) is selected from at least one of the groups consisting of silicon dioxide and titanium dioxide>
[0046] The composition comprising the calcined body of the present invention includes at least one selected from the group consisting of silicon dioxide and titanium oxide.
[0047] The silica (SiO2) is preferably high-purity silica with a purity of 99.8% or higher, and commercially available materials such as ultrafine anhydrous silica can be used. The average particle size of the silica is the same as that of composition (i).
[0048] "Titanium oxide" refers to titanium oxide (IV) (TiO2). The average particle size of titanium oxide is the same as that of composition (i).
[0049] Silica and titanium dioxide are porous, therefore it is believed that in addition to their own physical properties, they also have the effects of supporting components (iii) and arbitrary components (vi). Titanium dioxide is also considered to function as a photocatalyst.
[0050] As component (ii), silicon dioxide and titanium dioxide are preferably used in combination.
[0051] The content of component (ii) is preferably 30 to 70 parts by mass per 100 parts by mass of the composition, more preferably 40 to 65 parts by mass. If the content of component (ii) is within the above range, the generation of photons can be improved.
[0052] <Component (iii) is selected from at least one of the following groups: platinum, platinum compounds, palladium, palladium compounds, iridium, iridium compounds, rhodium, and rhodium compounds>
[0053] The composition comprising the calcined body of the present invention includes at least one selected from the group consisting of platinum, platinum compounds, palladium, palladium compounds, iridium, iridium compounds, rhodium, and rhodium compounds. Preferably, it includes at least one selected from the group consisting of platinum and platinum compounds.
[0054] It is believed that at least one of the following groups consisting of platinum, platinum compounds, palladium, palladium compounds, iridium, iridium compounds, rhodium, and rhodium compounds is the main component used for generating photons in the calcined body of the present invention.
[0055] Examples of compounds that can be classified as platinum, palladium, iridium, or rhodium compounds include organic acid salts, inorganic acid salts, halides, oxides, hydroxides, and ammonia compounds.
[0056] Component (iii) is preferably added in colloidal form. This is because so-called colloidal activation, which involves the adsorption of oxygen and hydrogen, can be expected. As component (iii), a dispersion colloid of component (iii) with an average particle size of about 0.7 to 4 nm (7 to 40 Å) is preferably used, for example, a dispersion colloid of component (iii) formed by dispersing component (iii) in a hydrochloric acid solution in a colloidal manner. The preparation method of the colloid of component (iii) can use commonly used methods. For example, a commercially available platinum colloidal solution containing 1% by mass of platinum can be used for the colloid of component (iii).
[0057] From the viewpoint of colloid activation, the component (iii) that contains 0.1 to 5% by mass in the colloid is preferred, more preferably 0.5 to 2% by mass, and even more preferably 0.8 to 1.2% by mass is preferred.
[0058] In 100 parts by weight of the composition of the present invention, component (iii) preferably comprises 0.0015 to 0.0500 parts by weight, more preferably 0.003 to 0.030 parts by weight, based on the amount of metal. If the content of component (iii) is within the above range, photons sufficient to exhibit health-enhancing effects can be generated.
[0059] <Component (iv) Silicon Nitride>
[0060] The composition that forms the calcined body of the present invention contains silicon nitride.
[0061] Silicon nitride of any composition is a ceramic having a Si3N4 composition. The ceramic is preferably obtained by sintering at 1780°C. It is believed that silicon nitride improves hydrogen activity and restricts the movement of hydrogen ions to a specific direction. Furthermore, it is believed that in addition to the inherent properties of the composition itself, it also has the effects of supporting composition (iii) and arbitrary composition (v).
[0062] Component (iv) is contained in 5 to 10 parts by mass, preferably 5 to 7 parts by mass, of 100 parts by mass of the composition of the present invention. If the content of component (iv) is within the above range, it can improve the generation of photons.
[0063] <Component (v) is selected from at least one of the groups consisting of silver, silver compounds, gold, and gold compounds>
[0064] The composition of the calcined body of the present invention preferably comprises at least one selected from the group consisting of silver, silver compounds, gold and gold compounds.
[0065] The optional ingredient (v) is preferably used in powder form, and may be commercially available powders of silver or gold and their compounds. The optional ingredient (v) more preferably includes at least one selected from the group consisting of silver and silver compounds.
[0066] In addition, the average particle size of component (v) depends on the product using the calcined body of the present invention and the manner of use. Ideally, it is preferably adjusted to a particle size of 2 μm or less, more preferably to 1.5 μm or less, and even more preferably to 1.0 μm or less, for example, 0.7 μm.
[0067] In 100 parts by weight of the composition of the present invention, the amount of gold or silver is preferably 0 to 30.0 parts by weight, more preferably 1.5 to 30.0 parts by weight, even more preferably 1.5 to 15.0 parts by weight, and particularly preferably 2.1 to 6.0 parts by weight. If the content of component (v) is within the above range, photon generation can be improved.
[0068] The composition that forms the calcined body of the present invention may further contain component (vi) barium feldspar and / or component (vii) blocky talc.
[0069] <Composition (vi) Barium Feldspar>
[0070] Barium feldspar of any composition is a ceramic having a structure of BaO·Al2O3·2SiO2. Well-known methods for manufacturing barium feldspar include, for example, calcination using BaCO3, α-Al2O3, and SiO2 as raw materials.
[0071] In 100 parts by weight of the composition of the present invention, component (vi) preferably comprises 0.1 to 5.0 parts by weight, more preferably 1.0 to 2.5 parts by weight.
[0072] <Composition (vii) Talc>
[0073] Lump talc of any composition is a ceramic having a MgO·SiO2 structure, preferably protoenstatite. Known manufacturing methods can be cited as examples of methods for producing lump talc, such as calcining talc as a raw material.
[0074] In 100 parts by weight of the composition of the present invention, component (vii) preferably comprises 0.1 to 5.0 parts by weight, more preferably 1.0 to 2.5 parts by weight.
[0075] <Other Ingredients>
[0076] In addition to the above-mentioned components, the composition of the calcined body of the present invention may also contain additives such as binders and stabilizers.
[0077] <Manufacturing Method>
[0078] The calcined body of the present invention can be manufactured by a manufacturing method having the following steps:
[0079] (Step 1) The step of mixing components (i), (ii) and (iv) to obtain a first mixture;
[0080] (Step 2) The step of adding component (iii) and any other component to the first mixture obtained in step 1 to obtain a second mixture; and
[0081] (Step 3) The second mixture obtained in Step 2 above is heated at 800~1000°C to obtain a calcined body.
[0082] First, a mixing process (step 1) is performed. Specifically, components (i), (ii), and (iv) are mixed to obtain a first mixture.
[0083] Next, a mixing process (step 2) is performed. Specifically, component (iii) and any other component are mixed in the first mixture obtained in step 1 to obtain a second mixture. In this step, component (iii) and any other component (v) can be heated and brought into contact with the first mixture, or preferably, the temperature and pressure at this time can be adjusted so that component (iii) and any other component (v) are loaded onto the pores and / or surfaces of components (i), (ii), and (iv).
[0084] Finally, the calcination process (step 3) is carried out. Specifically, the second mixture obtained in step 2 above is heated at 800~1000℃ for 15~20 minutes to obtain the calcined body.
[0085] Furthermore, the calcined body of the present invention can be manufactured as a particulate powder. The calcined body of the present invention is preferably granular, with an average particle size of less than 0.1 μm. It is believed that by keeping the average particle size within the above range, the amount of photons generated is increased. It should be noted that the average particle size is a value obtained by laser diffraction scattering.
[0086] As a method for forming the above-mentioned average particle size, examples include adjusting the particle size of the raw material; and using a bead mill to wet-crush the above-mentioned calcined body in the presence of alumina balls.
[0087] <Characteristics>
[0088] like Figure 1 and Figure 3 As shown, the calcined body of the present invention emits light, that is, it generates photons.
[0089] <Applications>
[0090] The calcined body of the present invention is intended for health promotion purposes.
[0091] More specifically, it can be said to have health-enhancing effects such as improving blood circulation, inhibiting lipid peroxidation, suppressing lactic acid production after exercise, and stabilizing the immune system. Further specific applications are expected to include improving menstrual cramps, cold intolerance, shoulder pain, rheumatism, arteriosclerosis, high cholesterol, diabetes, fatigue recovery, flu prevention, and microthrombosis.
[0092] The calcined body of the present invention generates photons as described above. Therefore, it is believed that if the calcined body of the present invention is used, NO will be generated in the human body. The generated NO relaxes blood vessels and affects blood circulation, etc. Therefore, it is believed that it is suitable for the above-mentioned health-enhancing applications.
[0093] <Product>
[0094] The calcined body of the present invention can be contained in fibers and films, etc.
[0095] When incorporated into chemical fibers and films, a masterbatch containing the calcined body of the present invention can also be used. Methods for manufacturing the masterbatch include forming the calcined body of the present invention into a powder and kneading it into a synthetic polymer, or forming it into a dispersion and mixing it into a synthetic polymer. In this case, the calcined body of the present invention in the masterbatch can be set to 0.1 to 25% by mass.
[0096] 1. Fiber
[0097] The calcined body of the present invention can be made into a product containing fibers.
[0098] Examples of fibers include natural fibers and chemical fibers. Examples of natural fibers include cotton, wool, silk, and hemp. Examples of chemical fibers include cellulose-based fibers, polyamide-based fibers such as nylon, polyvinyl alcohol-based fibers such as vinylon, polyvinylidene chloride-based fibers, polyvinyl chloride-based fibers, polyester-based fibers, acrylic-based fibers, polyolefin-based fibers, and polyurethane-based fibers. They can be used individually or in combination of two or more. For example, natural fibers can be blended with chemical fibers containing the calcined body of this invention.
[0099] To incorporate the calcined body of the present invention into fibers, it can be kneaded into the fibers or attached to the fiber surface. As a method for kneading the calcined body of the present invention into fibers, examples include mixing, for instance, 0.1 to 25% by mass, preferably 0.1 to 3% by mass, and more preferably 0.3 to 1.5% by mass of the calcined body of the present invention relative to the fibers, melting the fibers to form a mixture, and then spinning the mixture using common spinning methods, such as melt spinning, dry spinning, or wet spinning. Spinning is also preferably performed after manufacturing a masterbatch containing the calcined body of the present invention. As a method for attaching the calcined body of the present invention to the fiber surface, spraying, impregnation, or coating methods can be used.
[0100] In addition to the calcined body of the present invention, enzymes, hyaluronic acid and other moisturizing agents may also be incorporated into the fiber.
[0101] Fibers containing the calcined body of the present invention are suitable for use in bedding, clothing, etc.
[0102] 2. Film
[0103] Products containing the calcined body of the present invention within a thin film can be produced.
[0104] Examples of resins that can be used as films include thermoplastic resins such as polyolefins, polyvinyl chloride, polyvinylidene chloride, polyethylene terephthalate, and polyurethane.
[0105] As a method for incorporating the calcined body of the present invention into a film, one example is to add the powdered calcined body of the present invention to the above-mentioned resin in a molten state, mix them, and then form them using a known method. Alternatively, a masterbatch containing the calcined body of the present invention can be mixed with the above-mentioned thermoplastic resin and then formed.
[0106] Films containing the calcined body of the present invention are suitable for use in medical tapes.
[0107] It should be noted that in the manufacturing of the above-mentioned fibers and films, various additives such as catalysts, plasticizers, ultraviolet absorbers, fillers, colorants, anti-coloring agents, flame retardants, anti-leakage agents, stabilizers, heat resistant agents, and fluorescent whitening agents can be mixed as needed.
[0108] Example
[0109] The present invention will now be described in more detail by way of examples and comparative examples, but the present invention is not limited to these examples.
[0110] [Example 1] Manufacturing of calcined body (1)
[0111] The particle size of commercially available alumina, silicon dioxide, titanium dioxide, and silicon nitride was adjusted to be less than 1 μm. Then, 30 parts by mass each of alumina, silicon dioxide, and titanium dioxide, and 5 parts by mass of silicon nitride were mixed to obtain a first mixture.
[0112] 2.5 parts by mass (0.025 parts by mass based on platinum content) of a platinum colloidal solution containing 1% platinum (average particle size 40 Å) and 2.5 parts by mass of silver powder with a particle size of 0.2~1.0 μm and an average particle size of 0.7 μm were added to the first mixture to obtain a second mixture. The second mixture was heated at 800 °C for 20 minutes to obtain a calcined body.
[0113] The calcined body was pulverized by wet grinding in the presence of alumina balls using a bead mill. The average particle size of the pulverized calcined body, determined by laser diffraction scattering, was less than 0.1 μm.
[0114] The luminescence of the calcined body with an average particle size of less than 0.1 μm was measured. The results are presented in... Figure 1 .
[0115] [Comparative Example 1] Manufacturing of calcined body (2)
[0116] In Example 1, without using silicon nitride, a first mixture was obtained by mixing 31.67 parts by mass each of alumina, silicon dioxide and titanium dioxide. Otherwise, a calcined body with an average particle size of less than 0.1 μm was obtained in the same manner as in Example 1.
[0117] The luminescence of the calcined body without silicon nitride and with an average particle size of less than 0.1 μm was measured. The results are presented in... Figure 2 .
[0118] [Example 2] Manufacturing of calcined body (3)
[0119] The particle size of commercially available alumina, silicon dioxide, titanium dioxide, and silicon nitride was adjusted to be less than 1 μm. Then, 30 parts by mass each of alumina, silicon dioxide, and titanium dioxide, and 7 parts by mass of silicon nitride were mixed to obtain a first mixture.
[0120] To the first mixture, 2.5 parts by weight (0.025 parts by weight based on platinum content) of a platinum colloidal solution containing 1% platinum (average particle size 40 Å), 2.5 parts by weight of silver powder with a particle size of 0.2~1.0 μm and an average particle size of 0.7 μm, 1.5 parts by weight of pulverized barium feldspar (BaO·Al2O3·2SiO2) and 1.5 parts by weight of pulverized protoencite were added to obtain the second mixture.
[0121] The second mixture was heated at 800°C for 20 minutes to obtain the calcined body.
[0122] The calcined body was pulverized by wet grinding in the presence of alumina balls using a bead mill. The average particle size of the pulverized calcined body, determined by laser diffraction scattering, was less than 0.1 μm.
[0123] [Application Example 1]
[0124] A masterbatch was prepared from 6 parts by mass of the calcined body of Example 1 relative to 100 parts by mass of the polyester blend. This masterbatch, at 10% by mass relative to the polyester blend, was melt-spun to produce 75 denier and 30 denier filaments.
[0125] [Application Example 2]
[0126] Using the fibers obtained in Application Example 1, the following fabric is manufactured.
[0127] Fiber blend ratio: 30% fiber and 70% cotton in Example 1.
[0128] [Application Example 3]
[0129] Using the fibers obtained in Application Example 1, the following fabric is manufactured.
[0130] Fiber blending rate: 100% of the fiber used in Example 1.
[0131] The measured values in the examples were determined by the following methods.
[0132] [ Figure 1 and Figure 2 [Determination of luminescence] A masterbatch was prepared relative to 100 parts by weight of polyester blend and 6 parts by weight of the calcined body of Example 1 for determination.
[0133] Measurement apparatus: The instrument used was an ultra-weak emission spectrometer CLA-FS4 (manufactured by Tohoku Electronic Industrial Co., Ltd.: emission detection area 300~850nm, center wavelength 420nm) and a sample chamber CLS-ST4 (manufactured by Tohoku Electronic Industrial Co., Ltd.).
[0134] Measurement conditions: Place 2g of the above masterbatch into a φ50 stainless steel dish and measure the luminescence for 10 minutes in air at 100℃.
[0135] Three measurements were performed, and their average value is shown below. Figure 1 .
[0136] The luminescence amount was also measured similarly for the calcined body of Comparative Example 1. The results are shown below. Figure 2 .
[0137] [ Figure 3 [Determination of luminescence] A masterbatch was prepared relative to 100 parts by weight of polyester blend and 6 parts by weight of the calcined body of Example 1 for determination.
[0138] Measurement apparatus: The instrument used was an ultra-weak emission spectrometer CLA-FS5 (manufactured by Tohoku Electronic Industrial Co., Ltd.: emission detection area 300~650nm, center wavelength 420nm) and a sample chamber CLS-ST5 (manufactured by Tohoku Electronic Industrial Co., Ltd.).
[0139] Measurement conditions: Place 2g of the above masterbatch into a φ50 stainless steel dish and measure the luminescence for 10 minutes in air at 100℃.
[0140] Three measurements were performed, and their average value is shown below. Figure 3 .
[0141] [Determination of average particle size]
[0142] It is determined by laser diffraction scattering method.
[0143] Compare Figure 1 and Figure 2 It can be seen that, Figure 1 The calcined body of this application shown is different from that without silicon nitride. Figure 2 Compared to the calcined body, the peak value of photon luminescence is 1.3 times higher.
[0144] Compare Figure 1 and Figure 3 When the CLA-FS5 ultra-weak emission spectrometer is used instead of the CLA-FS4 ultra-weak emission spectrometer as the measuring device, the peak value of photon emission is more than doubled. Compared with the CLA-FS4, the CLA-FS5 ultra-weak emission spectrometer further improves the emission detection capability and sensitivity by narrowing the emission detection area around the center wavelength.
Claims
1. A calcined body comprising: (i) alumina; (ii) at least one selected from the group consisting of silicon dioxide and titanium oxide; (iii) at least one selected from the group consisting of platinum, platinum compounds, palladium, palladium compounds, iridium, iridium compounds, rhodium, and rhodium compounds; (iv) silicon nitride; and (v) at least one selected from the group consisting of silver, silver compounds, gold, and gold compounds. The composition contains 5 to 10 parts by weight of (iv) silicon nitride in 100 parts by weight.
2. The calcined body according to claim 1, further comprising (vi) barium feldspar.
3. The calcined body according to claim 1, further comprising (vii) block talc.
4. The calcined body according to claim 1, wherein it is granular and has an average particle size of less than 0.1 μm.
5. The calcined body according to claim 1, wherein, Component (iii) contains platinum or a platinum compound.
6. A fiber comprising the calcined body according to any one of claims 1 to 5.
7. A thin film comprising the calcined body according to any one of claims 1 to 5.
Citation Information
Patent Citations
JP1972012378U
Powder for far infrared radiation
JP1987184088A
Textile yarn provided with far infrared ray-emissive substance and production thereof
JP1991241025A
Yarn for woven fabric containing far infrared radiation substance and production thereof
JP1992073226A
Powder for radiation of infrared ray-weak energy and synthetic fiber containing same powder
JP1991190990A